Retinal Damage from Laser Pointer Misuse – Case Series from the Military Sector in Oman - Shenoy, Radha (Middle East Afr J Ophthalmol, 2015)
Laser pointers are practical and safe training tools when used properly. If used incorrectly they can cause ocular damage, potentially resulting in devastating vision loss. The ocular and visual morbidity can result in significant expenses for medical care and inability to work (temporarily or permanently) for civilians and military personnel. We present three cases of soldiers who experienced vision loss following exposure to laser pointers, while celebrating successfull football game.